An LEU-loaded long-life innovative sodium-cooled fast reactor (iSFR) with novel and passive safety devices. (September 2016) - Hartanto, Donny; Kim, Inhyung; Kim, Chihyung; Kim, Yonghee
Highlights: A conceptual design of a long-life LEU-loaded innovative SFR was presented. Core neutronics and thermal–hydraulics characteristics were investigated. Two passive safety devices FAST & SAFE were introduced to improve inherent safety. The coolant void reactivity issues can be resolved by adopting the FAST & SAFE. Abstract: This paper presents the neutronics conceptual design of a long-life 392.6 MWth innovative sodium-cooled fast reactor (iSFR). The iSFR, which was derived based on Korean Prototype Generation-IV sodium cooled fast reactor (PGSFR), was intended as an alternative fast reactor option while waiting for the availability and readiness of the fuel recycling technology in the Republic of Korea. The iSFR core was designed for a lifetime of over 20 EFPYs (effective full power years) and an average core discharged burnup greater than 100 GWd/MTHM. It was loaded with annular metallic low enriched uranium (LEU) fuels, which were arranged in eight rings of hexagonal assemblies and surrounded by three rings of PbO radial reflectors. The core neutronic performance and characteristics such as core lifetime, power profiles and thermal–hydraulics analysis, kinetics parameters and reactivity feedback coefficients, and cladding fast neutron fluence were analyzed by using McCARD Monte Carlo code and MATRA-LMR thermal–hydraulics sub-channel code. A balance of reactivity (BOR) analysis was also investigated to preliminary assess the safety capability of the iSFR against several unprotected transient scenarios. In addition, two new unique passive safety devices named FAST (Floating Absorber for Safety at Transient) and SAFE (Static Absorber Feedback Equipment) were also introduced and discussed in this paper.